Effects of a 12-Weeks Yoga Intervention on Motor and Cognitive Abilities of Preschool Children - Aleksić Veljković, Aleksandra; Katanić, Borko; Masanovic, Bojan (Frontiers in Pediatrics, 2021)
Since early childhood is regarded as an important period of motor and cognitive development, understanding the effects of physical activity on motor abilities and cognitive development in preschool children has major public health implications. This study investigates the effects of a 12 weeks’ yoga intervention program on motor and cognitive abilities in preschool children. Preschool children (n = 45; age 5 to 6 years) attending regular preschool programs were non-randomly assigned to yoga intervention (n = 23; 30 min sessions three times per week) or a control group (n = 22; no additional organized physical activity program). Exercise training for the intervention group included a yoga program. Motor abilities (BOT-2 subtests: fine motor integration, manual dexterity, balance, and bilateral coordination), and cognitive abilities (School Maturity Test subtests: visual memory, stacking cubes, and codes) were assessed before and after the intervention period in both groups. Data were analyzed using repeated-measures ANOVA. Participants in the intervention group improved fine motor integration (p=0.022), fine motor skills in general (0.029), bilateral coordination (0.000), balance (0.000), and body coordination (0.000). Preschool children’s participation in the preschool yoga intervention significantly improved their motor abilities, but not their cognitive abilities.